2014
DOI: 10.1051/0004-6361/201423504
|View full text |Cite
|
Sign up to set email alerts
|

Herschelview of the large-scale structure in the Chamaeleon dark clouds

Abstract: Context. The Chamaeleon molecular cloud complex is one of the nearest star-forming sites and encompasses three molecular clouds (Cha I, II, and III) that have a different star-formation history, from quiescent (Cha III) to actively forming stars (Cha II), and one that reaches the end of star-formation (Cha I). Aims. We aim at characterising the large-scale structure of the three sub-regions of the Chamaeleon molecular cloud complex by analysing new far-infrared images taken with the Herschel Space Observatory.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 64 publications
9
64
0
Order By: Relevance
“…The power-law distribution we find for all PDFs of the IRDCs in our sample is in accordance with the power-law tails found for IR-bright clouds (Lombardi et al 2008;Kainulainen et al 2009;Hill et al 2011;Schneider et al 2012Schneider et al , 2013Schneider et al , 2015Russeil et al 2013;Tremblin et al 2014;Alves de Oliveira et al 2014). In these studies, a clear turnover from a log-normal distribution for low column densities (typically from A v < 1 up to A v of a few magnitudes) into a power-law tail was observed.…”
Section: Global and Local Gravitational Collapse Of Irdcssupporting
confidence: 90%
“…The power-law distribution we find for all PDFs of the IRDCs in our sample is in accordance with the power-law tails found for IR-bright clouds (Lombardi et al 2008;Kainulainen et al 2009;Hill et al 2011;Schneider et al 2012Schneider et al , 2013Schneider et al , 2015Russeil et al 2013;Tremblin et al 2014;Alves de Oliveira et al 2014). In these studies, a clear turnover from a log-normal distribution for low column densities (typically from A v < 1 up to A v of a few magnitudes) into a power-law tail was observed.…”
Section: Global and Local Gravitational Collapse Of Irdcssupporting
confidence: 90%
“…First results from the Herschel Gould Belt Survey (HGBS) have confirmed the ubiquity of filaments in nearby clouds and suggested that these filaments play a central role in the formation of prestellar cores in low-mass star-forming regions (André et al 2010. The Herschel observations revealed a characteristic inner filament width of ∼0.1 pc, independent of the length or column density of the filaments (Arzoumanian et al 2011;Palmeirim et al 2013;Alves de Oliveira et al 2014;Koch & Rosolowsky 2015), and close to the sonic scale of turbulence in low-density molecular gas. The origin of this characteristic width is not yet understood well but is possibly connected to the process of filament formation by large-scale turbulent compression of interstellar material (Padoan et al 2001;Arzoumanian et al 2011;Federrath 2016).…”
Section: Introductionmentioning
confidence: 80%
“…On smaller scales, a comparison between CO maps (Goldsmith et al 2008), as well as CO velocity anisotropy , and the optical polarization revealed an alignment between the local magnetic field and quasi-parallel "striations" of neutral gas in several diffuse low-density subregions of the Taurus molecular cloud. The Herschel dust continuum maps of the Taurus and Chamaeleon clouds taken as part of the HGBS also show the presence of such low-density striations, oriented parallel to the ambient magnetic field and roughly perpendicular to denser, star-forming filaments (Palmeirim et al 2013;Alves de Oliveira et al 2014;Koch & Rosolowsky 2015). At lower resolution, the results of Planck Collaboration Int.…”
Section: Introductionmentioning
confidence: 95%
“…The observed PDFs show a lognormal distribution over a range of low column densities, typically between A v ∼ 0.5 to ∼4. A more or less lognormal distribution was reported for clouds (Lupus, Coalsack: Kainulainen et al 2009;Polaris: Schneider et al 2013; Chamaeleon III: Alves de Oliveira et al 2014) where none or only a few pre-or protostellar cores were detected. Herschel studies of several star-forming molecular clouds (Tremblin et al 2014;Schneider et al 2012Schneider et al , 2013 have shown that the lognormal part of the PDF broadens in the presence of external pressure (e.g., expanding H II regions) and that even a second peakindicating the compressed shell -can appear.…”
Section: Pdfs From Observationsmentioning
confidence: 90%